Republic of Moldova : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper analyzes the macroeconomic impact of workers' remittances on Moldova. The paper focuses on Moldova's labor emigration since the late-1990s using survey data designed to shed light on the economic and social consequences of migration. The survey results are broadly consistent both with the findings from balance-of-payments data and with the stylized facts in the labor migration literature. The paper also examines various indicators to assess the appropriateness of the current exchange rate level.